Comparative Analysis of Financial Performance of Bank and Non-Bank Financial Institutions: Case Study of PT Bank Maybank Indonesia Tbk and Pt Prudential Life Assurance for the 2023–2024 Period - Nurul Fadilah Aswar (Abadi Institute, 2026)
This study aims to analyze and compare the financial performance between bank and non-bank financial institutions in Indonesia with a case study of PT Bank Maybank Indonesia Tbk and PT Prudential Life Assurance for the 2023–2024 period. The research uses a quantitative descriptive approach with the analysis of financial statements which includes balance sheets, profit and loss, and financial ratios. The results show that banks have a more stable performance with diversified asset structures and consistent income, while non-bank financial institutions show high profitability but are more sensitive to market and investment risks. These differences reflect the characteristics of each institution's business model and funding sources. This research provides important implications for investors and regulators in understanding risks and opportunities in the financial sector